Implementasi Modul Kimia Pangan Melalui Pendekatan Etnokimia di SMK Negeri Aceh Timur Program Keahlian Tata Boga - Jofrishal Jofrishal*; Seprianto Seprianto (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
Implementation of learning modules is part of the development proses of ethnochemistry based modules. This study aims to find out the effect of the implementation of ethnochemical-based food chemistry modules on students through analysis of student understanding of integrated chemistry concepts, analysis of the effectiveness of learning processes in the classroom, and the level of understanding and awareness of ethnochemistry and the scientific process. This type of research is quantitative descriptive with a comparative approach using an experimental method with a control group. The sample determination was done by random sampling technique taken at one of the Vocational Schools in East Aceh on Food Expertise Program. Data collection is done through evaluating student learning outcomes using multiple choice questions, measuring learning effectiveness and understanding of ethnochemistry using observation sheets and structured interview sheets. The research results obtained student learning outcomes in the experimental class were on average higher than the control class, even though the results of statistical using t test did not show a significant difference. The score of the observation result of learning effectiveness in the experimental class is higher than the control class that is equal to 89,532 with very good criteria. Measurement of students' understanding of ethnochemistry after the application of the module obtained an increase of 40 points compared to before the application of the module. This shows an increase in students' understanding and awareness of ethnochemistry and the scientific process that take place in it and can strengthen the justification that learning modules with ethnochemical approaches are very well applied as teaching material.